Corticosteroid-induced remission and mycophenolate maintenance therapy in granulomatous lymphocytic interstitial lung disease: long-term, longitudinal change in lung function in a single-centre cohort. Issue 4 (17th October 2022) - Bintalib, Heba M.; Lowe, David M.; Mancuso, Gaia; Gkrepi, Georgia; Seneviratne, Suranjith L.; Burns, Siobhan O.; Hurst, John R.
Aim: The aim of the study was to evaluate the response in lung function to different treatment regimens for common variable immunodeficiency patients with granulomatous lymphocytic interstitial lung disease (GLILD). Method: A longitudinal retrospective cohort study was carried out. Patients were divided into three groups. To assess the response to different treatments, we compared baseline lung function with post-treatment tests. Results: 14 patients with GLILD were included, seven of whom were treated with acute corticosteroids for a mean duration of 132±65 days. Spirometry results were unchanged, but there was a significant improvement in diffusing capacity of the lung for carbon monoxide ( D LCO )% and transfer coefficient of the lung for carbon monoxide ( K CO )% (median change in D LCO %=7%, p=0.04, and K CO %=13%, p=0.02). Relapse occurred in three out of seven patients. Five patients were treated with long-term mycophenolate mofetil (MMF) with/without corticosteroids for a mean duration of 1277±917 days. No changes were found in spirometry; however, there was a significant increase in D LCO % and K CO % (median change in each of D LCO % and K CO %=10%, p=0.04). Four patients on steroids with MMF successfully weaned the prednisone dose over 12 months. Four patients never received immunosuppression therapy. A significant decline was found in their lung function assessed over 7.5 years. The median reduction in the forced vital capacity (FVC)%, forced expiratory volume in 1 s (FEV1 )% and D LCO % was 15%, 7% and 15%, equivalent to 2%, 1% and 2% per year, respectively. Conclusion: Corticosteroids improve gas transfer in GLILD, but patients often relapse. The use of MMF was associated with long-term effectiveness in GLILD and permits weaning of corticosteroids. A delay in initiating and continuing maintenance treatment could lead to disease progression. The use of MMF is associated with long-term effectiveness in GLILD and permits weaning of corticosteroids. A delay in initiating and continuing maintenance treatment could lead to disease progression. https://bit.ly/3PXShAd